Analisis Faktor-Faktor Pembelian Impulsif pada E-commerce Kecantikan - Salsabila, Rania Femi; Suyanto, AMA (Fakultas Ekonomi Universitas Samudra, 2022)
Beauty e-commerce often holds promos for people to purchase impulsively. The purpose of this study is to determine what factors can influence impulse buying on beauty e-commerce in Indonesia. This study uses quantitative methods, with the population are consumers who have purchased at beauty e-commerce. The number of respondents was 385 people who domiciles in big cities, small cities and metropolitan cities. The multivariate technique used exploratory factor analysis. The results show that there were ten new factors formed in impulsive purchases in beauty e-commerce, namely ease and organized, product trend, customer service, promo, pleasure, attraction, limited time, brand, shopping motivation, and recommendation factor. The most dominant factor among those new factors is ease and organized.